(untitled) (ARS, 2010)
Poéticas Digitais Group was created in 2002 in the Visual Arts Department at ECA-USP to create a multidisciplinary center, promoting the development of experimental projects and reflection on the impact of new technologies in the field of arts. The Group is an unfolding of the wAwRwT project started in 1995 by Gilbertto Prado and has as participants lecturers, artists, researchers and students. The aim of this article is to present some recent experiments such as "desluz", (2009/2010) and "amoreiras".